S1-Leitlinie der DGRh zur sequenziellen medikamentösen Therapie der rheumatoiden Arthritis 2012: adaptierte EULAR-Empfehlungen und aktualisierter Therapiealgorithmus - Krüger, Klaus; Lorenz, Hanns-Martin (Zeitschrift für Rheumatologie, 2012)
Following the EULAR recommendations published in 2010 German guidelines for the medical treatment of rheumatoid arthritis were developed based on an update of the systematic literature search and expert consensus. Methotrexate is the standard treatment option at the time of diagnosis, preferably in combination with low dose glucocorticoids. Combined disease-modifying antirheumatic drugs (DMARD) therapy should be considered in patients not responding within 12 weeks. Treatment with biologicals should be initiated in patients with persistent high activity no later than 6 months after conventional treatment and in exceptional situations (e.g. early destruction or unfavorable prognosis) even earlier. If treatment with biologicals remains ineffective, changing to another biological is recommended after 3-6 months. In cases of long-standing remission a controlled reduction of medical treatment can be considered.
Gesehen am 20.08.2018